Pengembangan Kelembagaan Kelompok Tani Gambut Di Kelurahan Sungai Pakning Kabupaten Bengkalis - Deasri Bella Yaumi; Zulkarnaini Zulkarnaini (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The Sungai Pakning sub-district has a vast area of peatland, which presents significant opportunities for the development of the agricultural sector. However, the potential of the region has not been fully realized by the local population. Farmers in this area face a range of challenges, including the adverse effects of climate change, limited access to resources, and a lack of knowledge about agricultural techniques suitable for peatlands. These obstacles have been the primary hindrances to enhancing agricultural productivity and optimizing the utilization of peatlands in Sungai Pakning Village. The objective of the study is to explore the possibilities of institutional development of farmer groups as a potential solution to improving the welfare of peat farmers in the village. The research employs a qualitative approach and field survey methods to identify the challenges faced by farmers. The findings of the research reveal that the institutional structure of farmer groups in this area is not entirely organized. Their role in supporting peat farmers can be improved by enhancing organizational structures, providing technical training, and increasing access to resources.